MANAJEMEN INDUSTRI RUMAH TANGGA PEMBUATAN GULA MERAH (Studi Kasus Pembuatan Gula Merah di Desa Matampa Kecamatan Ponre Kabupaten Bone) - Hasmidar Hasmidar (Agriplus, 2016)
Industry management was done with applying of management function such as planning, organizing, instruction, anf controlling In the application of management system applied in home industry management of brown sugar production in Mattampa, Ponre District of Bone Regency. It was implied application level of management function to manage and grow the home industry. This research was aimed to know and anlyze the application of management system toward the home industry growing  of brown sugar in Bone regency. This was a descriptive method with the all of brown sugar home industry Mattampa Ponre district of Bone regency as the sample. The result of this study showed that management application done by brown sugar home industry in Bone regency started from planning, organizing, instruction, and coordination were 0-100. The percentage of management system application through management function was the highest level 28,48%, then 17,22%, 45,64%, 13,92% and 11,26%. The growing of brown sugar home industry in agribusiness with the highest percentage 27,16%, then 16,05%, 14,81% and 13,58%. Key words: home industry, management system, brown sugar production